Overall survival after initial radiotherapy for brain metastases; a population based study of 2140 patients with non-small cell lung cancer. (3rd August 2021) - Karlsson, Astrid Telhaug; Hjermstad, Marianne Jensen; Omdahl, Therese; Aass, Nina; Skovlund, Eva; Hellebust, Taran P.; Johansen, Safora; Kaasa, Stein; Yri, Olav Erich
Abstract: Background: Brain metastases (BM) occur in about 30% of all patients with non-small cell lung cancer (NSCLC). BM treatment guidelines recommend more frequent use of stereotactic radiotherapy (SRT). Overall, studies report no difference in overall survival (OS) comparing SRT to whole-brain radiotherapy (WBRT). We examined survival after radiotherapy for BM in a population-based sample from the South-Eastern Norway Regional Health Authority treated 2006-2018. Methods: We reviewed electronic medical records of 2140 NSCLC patients treated with SRT or WBRT for BM from 2006–2018. Overall survival (OS) was compared to predicted survival according to the prognostic systems DS-GPA and Lung-molGPA. Results: Use of SRT increased during the period, from 19% (2006–2014) to 45% (2015–2018). Median OS for all patients was 3.0 months, increasing from 2.0 (2006) to 4.0 (2018). Median OS after SRT was 7.0 months ( n  = 435) and 3.0 months after WBRT ( n  = 1705). Twenty-seven percent of SRT patients and 50% of WBRT patients died within 90 days after start of RT. Age ≥70, male sex, KPS ≤70, non-adenocarcinoma histology, ECM present, multiple BM, and WBRT were associated with shorter survival ( p  < .001). Actual mOS corresponded best with predicted mOS by DS-GPA and Lung-molGPA for the SRT group. Conclusion: Overall survival after radiotherapy (RT) for BM improved during the study period, but only for patients treated with SRT. Survival after WBRT remains poor; its use should be questioned. DS-GPA and Lung-molGPA seem most useful in predicting prognosis considered for SRT.